KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR: STUDI PEMAHAMAN, SIKAP, DAN PERILAKU TANGGAP DARURAT MASYARAKAT KOTA MEDAN - Muhammad Farhan Muhaimin (SYMBOLE, 2025)
This study explores flood crisis management strategies developed by local communities through a bottom-up approach and community-driven crisis management perspective. The research investigates how communities in Medan City manage flood crises through three integrated phases: emergency response, post-disaster recovery, and long-term adaptation. Using descriptive qualitative methods with in-depth interviews, participatory observation, and local document analysis of flood-affected communities during the November 2025 disaster, this research identifies patterns of spontaneous responses grounded in indigenous local knowledge, mobilization of social networks through informal leadership, and collective learning that transforms adaptive community behaviors. The findings reveal that communities are not passive actors but active respondents who organize indigenous early warning systems, simple technology-based emergency communication, and mutual assistance as mechanisms for socio-economic recovery. This study emphasizes the critical importance of recognizing and strengthening community local capacity in collaborative and participatory disaster management policies that promote sustainable resilience and inclusive disaste r risk reduction.